DESIGN AND OPTIMIZATION OF TRANSMITTER LAMINATED SYNCHRONOUS RELUCTANCE MOTOR - Solak, Burak; Oner, Yasemin (IEEE, 2020)
In this study, a new Synchronous Reluctance Motor (SynRM) is designed with the same stator lamination as an induction motor. Here, losses were minimized and efficiency increased with a new rotor design There is no copper loss in SynRM rotors as in rotors of asynchronous motors and therefore rotor losses are minimized.. In this way, engine efficiency was improved by reducing engine losses. While designing, Ld / Lq ratio, which has an effect on engine performance, was taken into consideration. As a result of the parametric analysis made on the rotor lamination, it was decided to use the structure with 4 barriers. With the newly designed SynRM, it has been observed that the efficiency class of the asynchronous motor with IEI efficiency class according to IEC standards has increased to IE4.
Keywords: Engineering